2003
DOI: 10.1097/01.jom.0000071509.96740.dd
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress Among Female Flight Attendants

Abstract: We evaluated the presence of chronic job stressors among flight attendants (FAs) to examine the relationships between these job stressors and psychological distress and job dissatisfaction. Seventy-three female FAs (90% participation) employed at two commercial airlines completed a detailed questionnaire. Standard questions and scale measures were used to assess job stressors, psychological distress, and job dissatisfaction. The association between job stressors and these outcomes was evaluated using multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 15 publications
5
46
1
4
Order By: Relevance
“…This indicates (1) a remarkable load in most of the flights (as also noted by MacDonald, Deddens, Grajewski, Whelan, & Hurrell [23]) and (2) a reduced load for the 3-pilots-crew on the flights to Tokyo only; however, pilots as well as flight attendants had a 3-hour resting period during flight, but higher pNN50 values were evident only in pilots, for which other factors may be crucial; during flights, in colloquial conversations, pilots mentioned that the flight to Delhi is somewhat peculiar as they fly over the Middle East and the border between Pakistan and India, that area being not as quiet as, e.g., the route over the north pole. Thus one may speculate that the higher pNN50 values in pilots to Tokyo may reflect the response of a 3-pilots-crew on a long-haul flight, the relatively low pNN50 values in flight attendants may be related to task demands, and the low values in pilots to Delhi may correspond to characteristics of [20,21]) is a source of stress like the interior noise [24,25].…”
Section: Discussionsupporting
confidence: 65%
“…This indicates (1) a remarkable load in most of the flights (as also noted by MacDonald, Deddens, Grajewski, Whelan, & Hurrell [23]) and (2) a reduced load for the 3-pilots-crew on the flights to Tokyo only; however, pilots as well as flight attendants had a 3-hour resting period during flight, but higher pNN50 values were evident only in pilots, for which other factors may be crucial; during flights, in colloquial conversations, pilots mentioned that the flight to Delhi is somewhat peculiar as they fly over the Middle East and the border between Pakistan and India, that area being not as quiet as, e.g., the route over the north pole. Thus one may speculate that the higher pNN50 values in pilots to Tokyo may reflect the response of a 3-pilots-crew on a long-haul flight, the relatively low pNN50 values in flight attendants may be related to task demands, and the low values in pilots to Delhi may correspond to characteristics of [20,21]) is a source of stress like the interior noise [24,25].…”
Section: Discussionsupporting
confidence: 65%
“…Two early surveys explored job strain and fatigue, 1 2 and a recent study among American women flight attendants verified that fatigue is a major problem. 3 The latter study showed that job stressors such as mental and psychological demands, imbalance between job demands and outside obligations, low supervisor support, and job dissatisfaction predicted psychological distress. The results of this study suggested that interventions aimed at reducing conflicts between work and private life, at minimising job stressors, and at increasing social support for flight attendants may enhance their wellbeing and job satisfaction.…”
mentioning
confidence: 91%
“…The aim of this study was to clarify the association of broad aspects of job stress with occupational injury in small and medium-sized manufacturing factories. Perceived job stress was evaluated by the Japanese version of the Generic Job Stress Questionnaire (GJSQ) developed by the National Institute for Occupational Safety and Health (NIOSH, USA), which is a well-established means of measurement [Hurrell and McLaney, 1988;Haratani et al, 1996;MacDonald et al, 2003;Nakata et al, 2004a;Sakai et al, 2005]. Sociodemographics, lifestyle, physical/psychological conditions, and occupational factors were included as confounding variables.…”
Section: Introductionmentioning
confidence: 99%